Analysis of Development Level Company Profitability on PT. Harbor Indonesia (Persero)Tbk Branchbelawan - Ridho Octavian Nasution; Kiki Farida Ferine; Muhammad Isa Indrawan (Rowter Journal, 2022)
Financial statements are reports that show the company's financial condition at this time or in a certain period. Financial ratios are activities to compare numbers in financial statements by dividing one number by another. A profitability ratio is a ratio to assess the company's ability to seek profit. This ratio also provides a measure of the level of management effectiveness of a company. This is indicated by the profit generated from sales and investment income. The research approach in this study is a descriptive study. Descriptive analysis helps researchers to explain the characteristics of the subject under study, and examine various aspects of a particular phenomenon. The place of this research is PT Pelabuhan Indonesia I (Persero) Tbk. Belawan Branch and Time This research started in November 2016 until it was finished. This study analyzes the growth and development of profitability by using profitability ratios, namely: Net Profit Margin (Net Profit Margin), Basic Earning Power, Operating Profit Margin (Operating Profit Margin), Return on Total Assets (Return On Assets), and Return on Equity (Return On Equity). From the analysis of profitability ratios at PT Pelabuhan Indonesia I (Persero) Belawan Branch from 2011 to 2016. It can be concluded that the profitability ratio has increased from 2011 to 2015 and has decreased from 2015 to 2016. The 2015 ratio is the ratio the best from 2011 to 2014. This was due to the increased operating income from 2011 to 2015.